2021
DOI: 10.1161/hypertensionaha.120.16809
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression of Macrophages Underlies the Cardioprotective Effects of CST (Catestatin)

Abstract: Hypertension is associated with inflammation and excessive production of catecholamines. Hypertensive patients have reduced plasma levels of CST (catestatin)—a bioactive cleavage product of the prohormone CgA (chromogranin A). In mouse models, hypertension symptoms can be reduced by administration of CST, but the role of CST in the regulation of cardiovascular function is unknown. In this study, we generated mice with KO (knockout) of the region of the CgA gene coding for CST (CST-KO) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 67 publications
3
53
0
Order By: Relevance
“…The shifts observed in the microbial phyla in this study after treating WT mice with CST are in agreement with the findings of Rabbi et al, who also reported an increase in Bacteroidota and a decrease in Firmicutes, albeit a different route for the administration of CST and dosage, (Rabbi, Munyaka, and Eissa 2017). Low abundance of Bacteroidota, especially Bacteroides/Prevotella have been linked to obesity, and CST-KO mice were described to be insulin resistant and obese besides having elevated blood pressure 13,27 . In contrast, increased Bacteroidetes/Firmicutes ratio has been associated with IBD 28,29 , which is characterized by elevated levels of CST (Muntjewerff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The shifts observed in the microbial phyla in this study after treating WT mice with CST are in agreement with the findings of Rabbi et al, who also reported an increase in Bacteroidota and a decrease in Firmicutes, albeit a different route for the administration of CST and dosage, (Rabbi, Munyaka, and Eissa 2017). Low abundance of Bacteroidota, especially Bacteroides/Prevotella have been linked to obesity, and CST-KO mice were described to be insulin resistant and obese besides having elevated blood pressure 13,27 . In contrast, increased Bacteroidetes/Firmicutes ratio has been associated with IBD 28,29 , which is characterized by elevated levels of CST (Muntjewerff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the two peptides contribute to the biodefence and inflammatory response in vascular walls. Catestatin and vasostatin-1 induce the anti-inflammatory phenotype and suppress the inflammation in human macrophages [ 19 , 20 , 109 ].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Accordingly, the abovementioned mechanism of ChgA hyperglycosylation (leading to reduced catestatin levels) might operate in essential hypertension as well. Recent preclinical data corroborate that catestatin acts as an autocrine attenuator of cardiac inflammation in hypertension by reducing macrophage inflammation in the heart as catestatin-KO mice did not only develop a hypertensive phenotype, but also showed marked left ventricular hypertrophy, macrophage infiltration of the heart and adrenal glands, as well as elevated levels of proinflammatory cytokines and catecholamines [ 54 ]. This work was the first to show that the immunosuppression of macrophages is a driving mechanism behind the cardioprotective effects of catestatin.…”
Section: Role Of Catestatin In Various Cardiovascular Disordersmentioning
confidence: 90%